The effect of diurnal distribution of carbohydrates and fat on glycaemic control in humans: a randomized controlled trial - Kessler, Katharina; Hornemann, Silke; Petzke, Klaus J.; Kemper, Margrit; Kramer, Achim; Pfeiffer, Andreas F. H.; Pivovarova, Olga; Rudovich, Natalia (Scientific reports, 2017)
Diurnal carbohydrate and fat distribution modulates glycaemic control in rodents. In humans, the optimal timing of both macronutrients and its effects on glycaemic control after prolonged consumption are not studied in detail. In this cross-over trial, 29 non-obese men were randomized to two four-week diets: (1) carbohydrate-rich meals until 13.30 and fat-rich meals between 16.30 and 22.00 (HC/HF) versus (2) inverse sequence of meals (HF/HC). After each trial period two meal tolerance tests were performed, at 09.00 and 15.40, respectively, according to the previous intervention. On the HF/HC diet, whole-day glucose level was increased by 7.9% (p = 0.026) in subjects with impaired fasting glucose and/or impaired glucose tolerance (IFG/IGT, n = 11), and GLP-1 by 10.2% (p = 0.041) in normal glucose-tolerant subjects (NGT, n = 18). Diet effects on fasting GLP-1 (p = 0.009) and PYY (p = 0.034) levels were observed in IFG/IGT, but not in NGT. Afternoon decline of glucose tolerance was more pronounced in IFG/IGT and associated with a stronger decrease of postprandial GLP-1 and PYY levels, but not with changes of cortisol rhythm. In conclusion, the HF/HC diet shows an unfavourable effect on glycaemic control in IFG/IGT, but not in NGT subjects. Consequently, large, carbohydrate-rich dinners should be avoided, primarily by subjects with impaired glucose metabolism.